USE OF PEDAGOGICAL QUALIETRY METHODS IN TEACHING ECONOMICS (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The article is devoted to improving the quality of economic education using the methods of pedagogical qualimetry. Stages of the qualimetric process, information on the diagnosis and assessment of the educational process by methods of pedagogical qualimetry.